Frizzled 2‐induced epithelial‐mesenchymal transition correlates with vasculogenic mimicry, stemness, and Hippo signaling in hepatocellular carcinoma. Issue 4 (6th March 2019) - Ou, Huohui; Chen, Zhanjun; Xiang, Leyang; Fang, Yinghao; Xu, Yuyan; Liu, Qin; Hu, Zhigang; Li, Xianghong; Huang, Yu; Yang, Dinghua
Abstract : Prior observation has indicated that Frizzled 2 (FZD2)‐induced epithelial‐mesenchymal transition (EMT) could be a key step in metastasis and early recurrence of hepatocellular carcinoma (HCC). However, the mechanism underlying tumor development and progression due to aberrant FZD2 expression is poorly defined. Here, we provide evidence that FZD2 is a driver for EMT, cancer stem cell properties, and vasculogenic mimicry (VM) in HCC. We found that FZD2 was highly expressed in two cohorts of Chinese hepatitis B virus‐related HCC patients, and that high FZD2 expression was associated with poor prognosis. Concerning the mechanism, gain‐ and loss‐of‐function experiments showed the oncogenic action of FZD2 in HCC cell proliferation, apoptosis, migration, and invasion. Further investigations in vitro and in vivo suggested that FZD2 promotes the EMT process, enhances stem‐like properties, and confers VM capacity to HCC cells. Notably, integrative RNA sequencing analysis of FZD2‐knockdown cells indicated the enrichment of Hippo signaling pathway. Taken together, our data suggest for the first time that FZD2 could promote clinically relevant EMT, CD44 + stem‐like properties, and the VM phenotype in HCC involving a potential Hippo signaling pathway‐dependent mechanism, and should be considered as a promising therapeutic target for the treatment of HCC. Abstract : We report for the first time that Frizzled 2 (FZD2)‐induced epithelial‐mesenchymal transition might be associated with vasculogenic mimicry and cancer stem cells, and subsequently contribute to the progress and recurrence of HCC. and revealed a correlation between the Hippo pathway and FZD2, thus establishing an extensive basis and providing a rationale for studying the role of FZD2 in HCC.